PELATIHAN DAN WORKSHOP MUSIK PERKUSI DALAM MENINGKATKAN KREATIVITAS SENI PADA GURU ANAK USIA DINI DI TK IT ASH SHIDDIQIYYAH BERJAN KEC. GEBANG KAB. PURWOREJO - Yulianto; Kuni solihah; Siti Khumaidah; Fit Rofiah (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2023)
PAUD teachers become role models in various matters, especially in applying the art of drum band music to improve the skills of their students. This Community Service activity aims to conduct training and workshops on percussion art for PAUD teachers in Anggrek Cluster, Gebang, Purworejo Regency to increase teacher creativity. This service was carried out using the asset-based community method. The results of this service show that the teachers are enthusiastic about participating in the training and the teachers' creativity in practicing percussion art looks good and increases.